Improving Discoverability, Preventing Broken Links: Considerations for Land-Grant University Publishers - Mark Anderson-Wilk (Journal of Applied Communications, 2011)
Publishers of online resources, including Extension publishing units at land-grant universities, are generally concerned about the discoverability of the resources they publish. Broken links create an obstacle between potential audiences and Extension resources, and thus reduce discoverability. This study examines the feasibility of Extension publishers using metadata (information about resources), digital object identifiers (instead of URLs), and/or institutional repositories (in combination with Extension catalogs) to improve the discoverability of their published resources. The use of rich, standardized metadata is recommended as a best practice in digital publishing. The Digital Object Identifier System provides publishers with tools to ensure persistent discoverability; however, the cost and time requirements may be impediments for some Extension publishers. Institutional repositories such as DSpace are underutilized and offer many benefits for Extension publishers to consider. In particular, using an institutional repository may be a low-investment option for Extension publishers to provide both access to and preservation of digital resources.
Keywords: Publishers; feasibility; Dspac; digital resources; metadata